Mobile money and household food security in Uganda - Conrad Murendo; Meike Wollni (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2016)
Despite the fact that the use of mobile money technology has been spreading rapidly in developing countries, empirical studies on the broader welfare effects of the technology on rural households are still limited. Using household survey data, we analyse the effect of mobile money on household food security in Uganda. Unlike previous studies that rely on a single measure of food security, we measure food security using two indicators - a food insecurity index and food expenditures. To account for selection bias in mobile money use, we estimate treatment effects and instrumental variables regressions. Our results indicate that the use of mobile money per se as well as the volumes transferred are associated with a reduction in food insecurity. Furthermore, the use, frequency of use, and volumes of mobile money transferred are associated with increases in food expenditures. Policy interventions and strategies aiming to improve household food security should consider the promotion of mobile money among rural households in Uganda and other developing countries as a promising instrument.
Keywords: G29; I31; O16; O33; 330; mobile money; food security; households; Uganda